Effects of Water Flow Rate and Water Quality on Tilapia Culture in the Mae Ping River, Thailand - Niwooti Whangchai (Science Faculty of Chiang Mai University, 2019)
The aim of study was to find out how flow rates influence water quality and other related factors which may influence the risks of mass fish mortality events in cage aquaculture operations in the Ping River in Northern Thailand. Eight monitoring stations were located along the 120 km stretch of the river, and water was sampled every month over a period of one year. The study found significant differences in temperature, DO, pH, conductivity and water flow rate between the rainy season and dry season. High flow (floods) in rivers caused by torrential rains could damage fish cages, cause massive fish escapes and deaths. Observations of water flow rates during a spate revealed that at the rate of 294.8 m3/s and 270 m3/s, river cages were destroyed. On the other hand, low flows (drought) during summer season could cause fish stress resulting from low dissolved oxygen levels, especially in culture areas with many cages. Therefore, fish farmers need to improve the strength and stability of floating open-top cages, use aeration, or choose times and sites to rear fish that reduce risks of exposure to adverse water quality or flow conditions.